The known and unknown of post-pump chorea: a case report on robust steroid responsiveness implicating occult neuroinflammation - Iqbal, Muhammad; Zaman, Muizz; Ojha, Niranjan; Gau, Yung-Tian A.; Young, Eufrosina I. (Frontiers in Immunology, 2024)
Post-pump chorea (PPC) is characterized by the development of choreiform movements following cardiopulmonary bypass (CPB) surgery. PPC occurs almost exclusively in children, and its pathophysiology remains unclear. Here we present an adult case of PPC after bovine aortic valve replacement (AVR) which exhibited dramatic and reproducible response to steroid, suggesting the presence of occult neuroinflammation. This observation suggests a novel underlying mechanism in certain subgroups of PPC, which is likely a heterogeneous condition to start with. Further research into the pathomechanisms of PPC could offer insights into managing this otherwise symptomatic control-only condition.